Branding, Storytelling e Relações Públicas: as histórias estabelecendo relacionamentos entre marcas e consumidores - Gomes, Gabriel Martins [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
This paper related the concepts of Branding and Storytelling with the purpose to demonstrate how stories can help the mark set up a solid relationship with their public. As we speak of a relation that involves communication processes, the ideas conveyed in this paper seek demonstrate to the professionals in this area, in especial way, the public relations, that the Storytelling could be a very important tool to the process of management of the mark. Before it get into this point, some characteristic and changes of the society and of the cosumers, to evidence news challenges that up-to-dates organizations have to face. After present this context, it moves in the direction of the understanding of the concepts of mark and branding, related those with the activities of the public relations. The marks are introduced in this paper as icons that have a virtual memory able to transmit emotional burden and meanings for the consumers. To finilize this, it introduces the concept of Storytelling and you’re applicability in the organizations, especially in branding process. Your contribution is very important as we see in the stories that are able to get the attention of many

Este trabalho relaciona os conceitos de Branding e Storytelling, a fim de demonstrar como as histórias podem ajudar a marca a estabelecer um relacionamento sólido com seus públicos. Por se tratar de uma relação que envolve processos comunicacionais, as reflexões presentes neste trabalho buscam demonstrar aos profissionais que atuam nessa área, em especial aos relações – públicas que o Storytelling pode ser uma ferramenta muito importante no processo de gestão da marca. Antes de chegar nesse ponto, são apresentadas as características e transformações da sociedade e dos consumidores, afim de, evidenciar os novos desafios que as organizações atuais enfrentam. Após essa contextualização, parte-se para a apresentação do conceito de marca e branding relacionando-os às atividades de Relações Públicas. As marcas são apresentadas neste trabalho como ícones que possuem uma memória virtual capaz de transmitir cargas emocionais e significados para os consumidores. Para finalizar apresenta-se o conceito de Storytelling e sua aplicabilidade nas empresas, principalmente no processo de branding. Sua contribuição é muito importante uma vez que as histórias são capazes de conquistar a atenção dos públicos e transmitir de maneira menos
Keywords: Nomes comerciais; Contadores de história; Relações publicas; Marca registrada; Business names